2018
DOI: 10.12968/bjon.2018.27.sup20.s6
|View full text |Cite
|
Sign up to set email alerts
|

SICKLE as a holistic treatment approach to sickle cell disease related ulcers

Abstract: This article introduces a simple approach to adopt in the treatment of sickle cell disease (SCD) related ulcerations based on the acronym SICKLE, standing for Skin assessment, Infection control, Compression, Keep moving keep debriding, Local strapping and Endless support. This case report explains and describes each step used in the treatment of this challenging disease in a 24-year-old patient, achieving complete healing in 6 months in long-lasting SCD ulceration previously treated without results with many o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Previous observational studies have suggested that the addition of CS can increase the pressure at the retromalleolar area, promote healing, reduce pain, and increase QoL. 28 , 35 , 36 , 37 However, the evidence evaluating the use of CS is limited.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous observational studies have suggested that the addition of CS can increase the pressure at the retromalleolar area, promote healing, reduce pain, and increase QoL. 28 , 35 , 36 , 37 However, the evidence evaluating the use of CS is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Previous observational studies have suggested that the addition of CS can increase the pressure at the retromalleolar area, promote healing, reduce pain, and increase QoL. 28,[35][36][37] However, the evidence evaluating the use of CS is limited. This service evaluation set out to evaluate the use of CS to treat patients with retromalleolar LU in a specialist leg ulcer clinic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations